Implementasi Strategi Kampus Mengajar untuk Mengurangi Learning Loss Pada Siswa SMP Muhammadiyah Sumbang - Ramadhan, Aditya; Dwianto, Aji; Rahayu, Sari Mugi; Romadhona, Gita Aulia (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
This research aims to evaluate the implementation of various programs at Muhammadiyah Sumbang Middle School with a focus on several programs such as bibliophile, clever at numeracy, my dream school, PHBS and madding project. The research result showed that after this program there was a significant increase in student understanding with 60% of students showing better post-test result compared to 40% in the pre-test. This program also fosters the development of student's social skills such as communication and cooperation. Overall, the implementation of these programs has succeeded in improving the quality of learning both in terms of academics and student character development as well as creating a more interactive and supportive environment.